Mahseers in India: A review with focus on conservation and management - DINESH, K; C, NANDEESHA M; P, NAUTIYAL; P, AIYAPPA (The Indian Journal of Animal Sciences, 2010)
Mahseers inhabit the rivers and freshwater lakes of South and Southeast Asian countries. In India, the group is well distributed right from the Himalayas up to the rivers of the Western Ghats. Most of the species belong to the genus Tor. Owing to their excellent sporting quality, the mahseers have been variously called as the ‘king’, ‘lion’, ‘tiger’, ‘the great fighter’, etc., by the anglers. In certain parts of the country, it has also been even given the status of a ‘divine fish’. Due to the similarities in the morphometrics and meristics, difficulties have been encountered in the correct identification of this group of fishes and recently molecular techniques have been used to resolve such ambiguities. To the local fisher folk and the tribal people residing along the up-streams of rivers, mahseers have been of considerable importance as they contribute much to their livelihood as well as food security. Despite their abundance at one time, mahseers are declining rapidly in different parts of India making them a ‘threatened’ group. Breeding technology has helped in undertaking conservation programmes of the Himalayan mahseer (Tor putitora) and the Deccan mahseer (Tor khudree). Efforts have also been made to understand the nutritional requirements of these species and to culture these species along with other carps. Though the conventional farming of this fish is not promising because of the slow growth compared to the Indian and Chinese carps, however, by formulating practical diets and appropriate technologies there is scope to harness the potential of this group of fishes. The culture of mahseers has to be undertaken with a multifaceted approach considering their value in sport, food and aim at their conservation and scientific management. The involvement of the private sector like Tata Power Company Ltd., in the conservation of the mahseer has shown that long term commitment can bring desirable outputs. The Coorg Wildlife Society is also trying for the management of the group by promoting the ‘ecosystem based fish habitat conservation’. These examples clearly demonstrate the involvement of the private and public sectors with the peoples’ participation would provide the much needed support to protect this important group of fishes. In this review, an effort is made to assess the progress on various aspects of taxonomy, biology, nutrition, reproduction, aquaculture and conservation of mahseers. The opportunities available to improve the livelihood of people by increasing the research and development efforts on this group of fishes and its tourism potential are also discussed.